In defense of defensive measures - Sarig, Oded H.; Talmor, Eli (Journal of Corporate Finance, 1997)
We examine how measures that defend incumbent managers against replacement by rival managers affect the information generated in control contests and how this information is used in subsequent investment decisions. We show that commonly used defensive measures allow shareholders to make better investment decisions than they can make absent these measures. Consequently, the adoption of defensive measures can increase shareholders' wealth. We find that good managers are less defended than poor managers and that managers whose interests are closely aligned with those of shareholders (e.g., via options or bonus plans) are less defended and have more control over firm decisions than managers whose interests are not so well aligned with those of shareholders. We also show that the informational role of defensive measures depends on the relative uncertainty about the quality of both parties to a control contest, and relate the predictions to the empirical evidence in the literature.